Evaluation of cold pressed oilseed cakes - A potential by-product for valorization: Evaluation of cold pressed oilseed cakes - A potential by-product for valorization - APARNA KUNA; LAKSHMIPRASANNA KATA (Journal of Oilseeds Research, 2023)
In a sstudy taken up to evaluate the nutritional composition of cold pressed oilseed cakes, sesame and mustard oilseed cakes were richest sources of protein, fiber and minerals. The essential amino acids content among the oilseed cakes ranged between 32.98 to 41.05gm/100gm, with highest essential amino acid content in mustard seed cake. Oleic Acid (C18:1n9cis) and linoleic Acid (C18:2n6cis) acids were found in higher quantities among all the oilseed cakes. However anti-nutrients like oxalates, phytates and saponins were also present in all seed cakes with significantly higher content in sesame and mustard seed cakes indicating the need for various pre-treatments before using the oilseed cakes for various food formulations. The oil processing industry generates a large amount of oilseed cake every year and hence efforts must be aimed at minimizing and efficiently valorizing this nutritious byproduct to support the concept of zero waste.